Recent Developments in the Numerics of Nonlinear Hyperbolic Conservation Laws Lectures Presented at a Workshop at the Mathematical Research Institute Oberwolfach, Germany, Jan 15 - 21, 2012 - Ansorge, Rainer; Bijl, Hester; Meister, Andreas; Sonar, Thomas (Notes on Numerical Fluid Mechanics and Multidisciplinary Design,, 2013)
In January 2012 an Oberwolfach workshop took place on the topic of  recent developments in the numerics of partial differential equations. Focus was  laid on methods of high order and on applications in Computational Fluid Dynamics. The book covers most of the talks presented at this workshop.  .